(untitled) (International Journal of Language, Literacy and Translation, 2025)
The present study investigates the lexical choices of the translators in terms of gender issues discussed in the novel The Courtesan of Lucknow (Umrao Jan Ada) translated by Khushwant Singh and M. A. Husaini. The study aims to analyze the ideologically loaded lexis (related to gender issues) of the novel with its translation. The aim is to further examine and find out how the lexical choices of the translators manipulate the original idea of the writer. The study employs Critical Discourse Analysis (CDA) as its theoretical and analytical framework for ideological manipulation of gender issues. The findings reveal that the use of different lexical choices of the translators has changed the ideological stance of the writer. This study will contribute both to the discipline of translation studies and literary translation. The novel has been studied from the perspective of feminist and literary aesthetics but the comparative aspect of both texts from a gender perspective is lacking. Therefore, the current study is an attempt to examine the ideological manipulation of gender issues of both source and target texts at the lexical level. The findings reveal that the translators have misrepresented the gender issues.